Pengaruh Implementasi Pengembangan Bahan Ajar Bahasa Indonesia Berbasis Permainan Edukasi Terhadap Keterampilan Menulis Siswa SMP Negeri 1 Peusangan - Zamharira, Zamharira; Astuti, Nia; Isnani, Wirdatul (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
The purpose of this study is to ascertain how employing educational game-based learning resources affects and improves seventh-grade students' ability to write narrative texts at SMP Negeri 1 Peusangan Selatan. A pretest-posttest control group design is employed, along with a quantitative, quasi-experimental research methodology. Sixty students, split into two classes—the experimental class and the control class—make up the research sample. Before and after therapy, a writing skills exam for narrative texts serves as the data gathering tool. Data analysis techniques are conducted through descriptive statistical tests, normality tests (Kolmogorov-Smirnov), homogeneity tests (Levene’s Test), N-Gain tests to see effectiveness, and t-tests (Independent Sample T-Test) to test the hypothesis. According to the findings, pupils in the experimental class significantly outperformed those in the control group. According to the t-test results, there is a substantial impact of employing educational game-based teaching resources on writing skills, with a significance level of 0.000 < 0.05. Furthermore, the experimental class's average improvement in writing abilities (77.85%) is categorized as strong by the N-Gain findings, whereas the control group only achieved 52.87%. According to the study's findings, junior high school students' writing abilities in narrative texts may be enhanced through the usage of instructional game-based tools.